Preparation and characterization of polymorphs of the glucocorticoid deflazacort - Kassuha, Diego Enrique (2014)
The polymorphism of new and old active pharmaceutical ingredients (APIs) is of great importance due to performance, stability and processability aspects. The objective of this study was to investigate the polymorphism of deflazacort (DEF), a glucocorticoid discovered >40 years ago, since this phenomenon has not been previously investigated for this API. Using different methods for solid form screening, it was determined for the first time that DEF is able to exist as three forms: a crystalline (DEF-1); a hydrated X-ray amorphous (DEF-t-bw) and an anhydrous amorphous phase (DEF-g) obtained from manually grinding DEF-1. The in vitro and in vivo dissolution rates (DRs) of DEF-1 and DEF-t-bw, which were measured using the rotating disk method in water at 37 °C and the pellet implantation technique in rats, respectively, indicated that DEF-t-bw exhibited slightly faster in vitro and in vivo DRs than those of the crystalline form, but the values were not significantly different. In addition, it was determined that DEF-t-bw devitrifies to DEF-1 by the effect of pressure, humidity and heat. It was concluded that DEF is glucorticoid with low tendency to exhibit different crystalline forms and that DEF-t-bw has no advantages over DEF-1 in terms of solubility, DRs and solid-state stability.